2023
DOI: 10.1039/d3sc00168g
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative matching of crystal structures to experimental powder diffractograms

Abstract: The identification and classification of crystal structures is fundamental in materials science, as the crystal structure is an inherent factor of what gives solid materials their properties. Being able to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“… 40 We therefore assessed the possibility of comparing the powder X-ray diffraction patterns generated by the automated robotic workflow against structure sets of putative crystal structures generated by CSP. From sample 1 for benzimidazole and ROY, we found that comparison of the experimental data against the low energy CSP structures using the variable-cell experimental powder difference (VC-xPWDF) method 41 identifies the predicted crystal structure as the observed polymorph; that is, alpha benzimidazole ( Fig. 5A ) has the most similar simulated powder X-ray diffraction pattern.…”
Section: Polymorph Matching Against Crystal Structure Prediction Data...mentioning
confidence: 99%
“… 40 We therefore assessed the possibility of comparing the powder X-ray diffraction patterns generated by the automated robotic workflow against structure sets of putative crystal structures generated by CSP. From sample 1 for benzimidazole and ROY, we found that comparison of the experimental data against the low energy CSP structures using the variable-cell experimental powder difference (VC-xPWDF) method 41 identifies the predicted crystal structure as the observed polymorph; that is, alpha benzimidazole ( Fig. 5A ) has the most similar simulated powder X-ray diffraction pattern.…”
Section: Polymorph Matching Against Crystal Structure Prediction Data...mentioning
confidence: 99%
“…VC-xPWDF is a recently developed code that allows for the accurate comparison of a simulated powder pattern (typically from an experimentally obtained crystal structure) with an experimental pattern. 35 The input crystal structure is converted to its Niggli reduced cell and transformed into possible unit cell bases that may be coincident with the given unit cell of the experimental PXRD pattern. Each candidate unit cell basis is deformed to match that of the PXRD data to identify the matching cell, ultimately yielding the measure of dissimilarity of the best matching cell, which is commonly referred to as the VC-xPWDF score.…”
mentioning
confidence: 99%